Post caesarean section complication and its management in Dhaka medical college hospital - Das, Mita; Ghosh, Abanti; Rani Ghosh, Suchita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The increase in the rate of caesarian sections globally is intimately related to the development of the women access to this procedure when required. But it is still related to the indiscriminate use without medical indication. This has fulminated in the recent efforts to reduce these rates while incorporating the obstetric preferences of women. Objective of the current study was to find out the predisposing factors for caesarian complications and to observe its management pattern. Methods: This was a cross sectional observational and descriptive study performed in the department of obstetrics and gynecology, Dhaka medical college hospital, Dhaka from January2019 to June 2019. All mothers admitted for elective and emergency cesarean section were selected by purposive sampling. Thereafter, they were scrutinized according to eligibility criteria and 100 patients were finalized. A pre-tested, observation based, peer-reviewed data collection sheet was prepared before study. Data regarding clinical, biochemical and surgical profile were recorded. Results: The mean age of the respondents was 25.96±4.43 (age range: 17-39) years. Among 100 mothers, 59% underwent elective and 41% underwent emergency cesarean section. 67% had uneventful outcome after LSCS. Rest 33% had post cesarean section complications. Among them 33% mother who had complications, 19 (57.57%), 12 (36.36%), 10 (30.30%) and 8(24.24%) had wound gap, UTI, GIT complications and haemorrhage respectively. 3 (9.09%) each suffered from thromboembolic complications and septic thrombophlebitis. Only one (3.03%) experienced DIC. Out of 33 complicated cases; 27 (81.81%) required treatment with injection oxytocin, blood transfusion, condom catheterization and 10 (30.30%) required secondary closure. Among them 4 (12.12%) underwent mass closure and received antithrombotic drug. One (3.03%) each underwent excision sinus tract and re-laparotomy. Conclusions: Caesarean section complications can result in death or morbidity. Despite advances in technology and expertise, wound infection or wound gap remains the most common post-c-section complication. It is critical to successfully manage complications after cesarean section in order to reduce morbidity and mortality among mothers.